Composite Index of Anthropometric Failure and Early Childhood Cognitive Development Based on the 2018 Indonesian Basic Health Research Data - Zamrudiani, Safira; Wahab, Abdul; Harisaputra, Rosalia Kurniawati (Kesmas, 2023)
Delays in early childhood cognitive development may have profound long-term implications on health and life expectancy. Optimal nutrition supports early life development, including a child's cognitive development. This study aimed to determine the association between the Composite Index of Anthropometric Failure and early childhood cognitive development among children aged 36-59 months in Indonesia. This cross-sectional study utilized data from the 2018 Indonesian Basic Health Research that involved 18,027 participants aged 36-59 months. This study outcome demonstrated that children who were stunted-underweight were potentially susceptible to delayed cognitive development compared to those with normal nutritional status (aOR = 1.30; 95% CI = 1.12–1.51) after controlling for child’s age, sex, vitamin A supplementation, antenatal care visits, gestational age, access to drinking water and sanitation (combined risk), maternal’s education and mental health (combined risk), maternal’s occupation and number of household members (combined risk). In summary, malnourished children are vulnerable to impaired physical growth and potential delays in early cognitive development.